The expensive-tissue hypothesis may help explain brain-size reduction during domestication. Issue 1 (31st December 2022) - Lesch, Raffaela; Kotrschal, Kurt; Kitchener, Andrew C.; Fitch, W. Tecumseh; Kotrschal, Alexander
ABSTRACT: Morphological traits, such as white patches, floppy ears and curly tails, are ubiquitous in domestic animals and are referred to as the 'domestication syndrome'. A commonly discussed hypothesis that has the potential to provide a unifying explanation for these traits is the 'neural crest/domestication syndrome hypothesis'. Although this hypothesis has the potential to explain most traits of the domestication syndrome, it only has an indirect connection to the reduction of brain size, which is a typical trait of domestic animals. We discuss how the expensive-tissue hypothesis might help explain brain-size reduction in domestication.